(3GdcGajs - (3Gdcdjfj, GdQGRj, GdSdSdj, GdHZOGOj, CHh LYaQ, eMeO Hf jYbhH Hf ESMGb, J (B329 (3g`s ((3NVQ Hf RjGQI GdMSjfjs)
(3ChdgG (B:s
(3eHJhQI GdChd, hChd GdehLhO efgG bhdg(B: ... (3Yf GdaVjd Hf jSGQ bGd SCdJ CHG YHO Gddg Ydjg GdSdGe Yf bhd Gddg JHGQc hJYGdi (B{ (3jhe fOYh cd CfGS HEeGege (B} (3abGd(B: (3jG aVjd GYQa EeGec aEfc EPG YQaJ EeGec dG jVQc JbOe gPG GdCeQ Ch JCNQ(B...s
(3BNQgG (B:s
(3Yf CMeO Hf YeQ bGd bGd CHh LYaQ Y hCJGg QLd abGd Efce Cgd HjJ QMeI GNJUce Gddg JHGQc hJYGdi HgG, abGd dg(B: (3cPdc fMf hGdMeO ddg dG fON CMOG aj VdGdI hdG fNQLg ef gOi(B...(3Je cJGH GdQhVI ef GdcGaj hgh BNQ GdCUhd(B...s
(3aj BNQgG QSGdI JTJed Ydi eLehYI CNHGQ jQhjgG SdeGf GdaGQSjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B7(3,U(B145s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B775s
(3gOjI GdYGQajf(B:(3L(B2(3,U(B35s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs